1991
DOI: 10.1111/j.1528-1157.1991.tb04694.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Profiles of the Potent and Orally Active GABA Uptake Inhibitors SK&F 89976‐A and SK&F 100330‐A and Four Prototype Antiepileptic Drugs in Mice and Rats

Abstract: The anticonvulsant profiles of two potent and orally active gamma-aminobutyric acid (GABA) uptake inhibitors, 1-(4,4-diphenyl-3-butenyl)-3-piperidine-carboxylic acid hydrochloride (SK&F 89976-A) and 1-(4,4-diphenyl-3-butenyl)-1,2,5,6-tetrahydro-3-pyridine-carboxylic acid hydrochloride (SK&F 100330-A), were determined with a battery of well-standardized tests in mice and rats and compared with the profiles of phenytoin (PHT), carbamazepine (CBZ), valproate (VPA) and clonazepam (CZP) when subjected to the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…In support of this principle, a number of GAT1-selective inhibitors have been developed and demonstrated to possess anticonvulsant activity in animal seizure models (Swinyard et al, 1991;Pavia et al, 1992;Suzdak and Jansen, 1995;White et al, 2002;Dalby, 2003). For example, the first peripherally active GABA uptake inhibitor was SKF 89976A [(R)-N-(4,4-diphenyl-3-butenyl) nipecotic acid], an N-substituted diphenyl butenyl analog of nipecotic acid (Swinyard et al, 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this principle, a number of GAT1-selective inhibitors have been developed and demonstrated to possess anticonvulsant activity in animal seizure models (Swinyard et al, 1991;Pavia et al, 1992;Suzdak and Jansen, 1995;White et al, 2002;Dalby, 2003). For example, the first peripherally active GABA uptake inhibitor was SKF 89976A [(R)-N-(4,4-diphenyl-3-butenyl) nipecotic acid], an N-substituted diphenyl butenyl analog of nipecotic acid (Swinyard et al, 1991).…”
mentioning
confidence: 99%
“…For example, the first peripherally active GABA uptake inhibitor was SKF 89976A [(R)-N-(4,4-diphenyl-3-butenyl) nipecotic acid], an N-substituted diphenyl butenyl analog of nipecotic acid (Swinyard et al, 1991). The corresponding analogs of guvacine, SKF 100330A [N-(4,4-diphenyl-3-butenyl)guvacine] and methoxy]ethyl guvacine], supported the principle that modulation of GABA transport would result in an anticonvulsant action (Swinyard et al, 1991;Pavia et al, 1992). Unfortunately, subsequent clinical trials with CI-966 revealed the potential for serious psychotic adverse effects in certain patients (Radulovic et al, 1993).…”
mentioning
confidence: 99%
“…The bath solution contained (mM): 120 NaCl, 4.7 KCl, 1-2 KH2PO4, 1-2 MgSO4, 2-2 CaCl2, 10 Hepes, 10 dextrose; pH 7-4 and osmolarity, 300 mosmol F-'. Wolf & Bondinell, 1991). GABA-free solution was exchanged for GABAcontaining solutions by a peristaltic pump (flow rate, 1 ml min-).…”
mentioning
confidence: 99%
“…Efforts to develop specific inhibitors of the GABA transporters have led to the identification of multiple compounds that have been shown to possess anticonvulsant activity in preclinical animal seizure models (Yunger et al, 1984;Krogsgaard-Larsen et al, 1987;Swinyard et al, 1991;White et al, 1993;Borden et al, 1994;Suzdak, 1995;Bolvig et al, 1999;Schousboe et al, 2004a;White et al, 2005). EF1502 (N-[4,4-bis(3-methyl-2-thienyl)-3-butenyl]-4-(methylamino-4,5,6,7-tetrahydrobenzo[d]isoxazol-3-ol), the Nsubstituted analogue of exo- 5,6,isoxazol-3-ol) noncompetitively inhibits both GAT1 and GAT2 (White et al, 2005;Clausen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%